Factors Affecting Mothers on Basic Immunization Status in Infants Aged 12-24 Months in Baruara Village - Munarni Simatupang (International Journal of Public Health Excellence (IJPHE), 2023)
Immunization is an act of providing immunity to children against diseases that could have been prevented by immunization before they were 12 months old, namely tuberculosis, polio, hepatitis B, diphtheria, pertussis, tetanus, and measles. Complete and regular basic immunization by getting all types of basic immunization when a child is less than 11 months old can reduce the morbidity and mortality of children under five by around 80-95%. Incomplete basic immunization can only provide maximum protection of 25-40%. The role of a mother in the immunization program is very important, because the use of health facilities by infants/children is related to factors that affect the mother. The purpose of this study was to determine the relationship between the factors that influence the mother's basic immunization status in infants aged 12-24 months. This study used a descriptive correlation design with a cross sectional approach. The number of samples in this study were 40 people. Sampling using the total population. This research was conducted in Baruara Village, Balige District, Toba Regency in March-May 2023. The instrument in this research was a questionnaire. Data analysis used chi-square. From the results of the study it was concluded that there was a significant relationship between maternal age with p=0.001, education with p=0.004, employment with p=0.001, number of children with p=0.000, and knowledge with p=0.000 to basic immunization status. From this research it is hoped that health workers will improve the quality of health services, health promotion efforts in the form of social support, namely improving the quality of health education, providing motivation in utilizing health services, especially immunization.